Analisis Pengendalian Persediaan Bahan Baku Kerupuk Mentah Potato Dan Kentang Keriting Menggunakan Metode Economic Order Quantity (EOQ) - Khoirul Hidayat; Jainuril Efendi; Raden Faridz (Performa: Media Ilmiah Teknik Industri, 2019)
The increase in the food industrial sector over the year making food producers experience tighter competition. In this era of intense competition in the food industry, raw material inventory control in PT. Surya Indah Food Multirasa is still facing a problem of lacking raw material in potatoes and curly potatoes every year, which affects in sale loss. This study is conducted to find out the precise amount of order in every raw material purchase, so there is no lack of raw material, at a lower cost. This study uses the Economic Order Quantity (EOQ) method for analyzing raw material control for potatoes and curly potatoes. Comparing the uses of company policy and EOQ. EOQ analysis calculation followed by conducting safety stock (SS) analysis, maximum inventory (MI) analysis, Total Inventory Cost (TIC) analysis, and reorder point (ROP) analysis, therefore, optimal stock for the company can be discovered. The result of EOQ analysis showed that the EOQ method is more efficient than company policy with TIC average difference for potato’s raw material that is Rp. 856.124 and curly potatoes raw material that is Rp. 1.065.989. The average EOQ value of potato’s raw material is 344 kg while curly potatoes are 234 kg. Next is the average SS value for potato raw material is 75 kg while curly potatoes are 35 kg, and the average ROP value for potato raw is 123 kg while curly potatoes are 58 kg. This research also performs forecasting using Winter’s method so that data demand for the year of 2019 can be discovered. The forecast result with the EOQ method for the year 2019 is 371 kg for potato's raw material and 258 kg for curly potatoes.